2011
DOI: 10.4061/2011/615087
|View full text |Cite
|
Sign up to set email alerts
|

Early Heparin Administration Reduces Risk for Left Atrial Thrombus Formation during Atrial Fibrillation Ablation Procedures

Abstract: Objective. Despite the use of anticoagulation during left atrial (LA) ablation procedures, ischemic cerebrovascular accidents (CVAs) are recognized as a serious complication. Heparin is usually given after safe transseptal access has been obtained, resulting in a short unprotected dwell time of catheters within the LA, which may account for CVAs. We investigated the frequency of CVAs and LA thrombus formation as detected by intracardiac ultrasound (ICE) depending on the timing of heparin administration. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…One recommendation of the task force (Table 4) is that heparin should be administered prior to or immediately following transseptal puncture during AF ablation procedures and adjusted to achieve and maintain a target ACT (activated clotting time) of 300 to 400 s. This recommendation reflects the well-established observation that thrombi can form on the transseptal sheath and/or electrode catheter almost immediately after crossing the septum and that early heparinization substantially decreases this risk [318,[381][382][383][384][409][410][411]. More than 50% of the task force members give heparin prior to the transseptal puncture.…”
Section: Intraprocedural Anticoagulationmentioning
confidence: 95%
“…One recommendation of the task force (Table 4) is that heparin should be administered prior to or immediately following transseptal puncture during AF ablation procedures and adjusted to achieve and maintain a target ACT (activated clotting time) of 300 to 400 s. This recommendation reflects the well-established observation that thrombi can form on the transseptal sheath and/or electrode catheter almost immediately after crossing the septum and that early heparinization substantially decreases this risk [318,[381][382][383][384][409][410][411]. More than 50% of the task force members give heparin prior to the transseptal puncture.…”
Section: Intraprocedural Anticoagulationmentioning
confidence: 95%
“…It has been observed that thrombi can form on the transseptal sheath and/or the electrode catheter almost immediately after crossing the septum and that early heparinization substantially decreases this risk. 768 , 802 , 803 , 804 , 846 , 847 , 848 A recent meta-analysis of more than 7000 patients supports this recommendation, showing that performing ablation of AF with a target ACT >300 seconds decreases the risk of thromboembolic complications without increasing the risk of bleeding. 849 Seventy-seven percent of the writing group members administer heparin prior to the transseptal puncture.…”
Section: Section 7: Technical Aspects Of Ablation To Maximize Safety mentioning
confidence: 96%
“… IIb C-EO 381 , 382 , 383 , 384 , 385 , 386 During ablation Heparin should be administered prior to or immediately following transseptal puncture during AF catheter ablation procedures and adjusted to achieve and maintain an ACT of at least 300 seconds. I B-NR 369 , 380 , 381 , 382 , 387 , 388 , 389 , 390 , 391 , 392 , 393 Administration of protamine following AF catheter ablation to reverse heparin is reasonable. IIa B-NR 394 Postablation In patients who are not therapeutically anticoagulated prior to catheter ablation of AF and in whom warfarin will be used for anticoagulation postablation, low molecular weight heparin or intravenous heparin should be used as a bridge for initiation of systemic anticoagulation with warfarin following AF ablation.…”
Section: Section 7: Technical Aspects Of Ablation To Maximize Safety mentioning
confidence: 99%